THE IMPLEMENTATION OF ISLAMIC BUSINESS PRINCIPLES IN SHARIA LAUNDRY BUSINESS "MR. CLING CIAMIS" - Roni Romli; Dede Husni Mubarok; Haqibul Mujib (Syari'ah Economics, 2022)
This study aims to determine the application of Islamic economic principles in the development of the Sharia laundry business "Mr. Cling Ciamis". This qualitative research with descriptive method is based on data from interviews and documentation. The results of the study conclude that the Islamic economic values applied by Laundry Syariah "Mr. Cling Ciamis" are monotheism, justice, free will, and responsibility have been implemented properly. In addition, the application of Islamic business principles continues to increase in line with progress or good business development. The development of the "Mr. Cling" Laundry business can be seen from the addition of business branches and the presence of several "Mr. Cling" Laundry agents in several places. The aspects of the application of Islamic economics are viewed from several indicators: marketing, human resources, and social.